Effects of the ratio between pigment and bleaching gel on the fracture resistance and dentin microhardness of endodontically treated teeth - Galloza, Marina O.G. [UNESP]; Jordão-Basso, Keren C.F. [UNESP]; Bandeca, Matheus C.; Costa, Samuel O.; Borges, Alvaro H.; Tonetto, Mateus R.; Tirintan, Fabio C.; Keine, Kátia C. [UNESP]; Kuga, Milton C. [UNESP] (Jaypee Brothers Medical Publishing, 2017)
Introduction: The aim of this study was to evaluate the effects of bleaching gel using 35% hydrogen peroxide (HP), associated with red carmine pigment (RC), in the 3:1 or 1:1 ratio, on fracture resistance and dentin microhardness of endodontically treated teeth. Materials and methods: A total of 40 lower incisors were endodontically treated and divided into four groups (n = 10), according to the bleaching protocol: G1 (HP3), 35% HP + RC (3:1); G2 (HP1), 35% HP + RC (1:1); G3 (positive), 38% HP; and G4 (negative), unbleached. Four dental bleaching sessions were performed. The dental crowns were restored after the last session and submitted to the fracture resistance test. Totally, 60 specimens from the endodontically treated lower incisor crowns were prepared to evaluate the effects on dentin microhardness. The analysis was measured (in Knoop) prior to and after the last dental bleaching session using similar bleaching protocols. Results: G2 presented the lowest fracture resistance (p < 0.05). The other groups were similar to each other (p > 0.05). No difference was observed in the reduction of dentin microhardness among the groups (p > 0.05). Conclusion:A 1:1 ratio (bleaching gel:pigment) caused a significant fracture resistance reduction in relation to the other protocols. No effect on the dentin microhardness reduction was observed. Clinical significance: The pigment addition to the bleaching agent accelerates the bleaching chemical reaction. However no studies have evaluated the ideal proportion to optimize tooth bleaching.
Keywords: Endodontics; Fracture; Hydrogen peroxide; Tooth bleaching